THE ROLE OF RELIGIOUS COPING TOWARD FEAR OF FAILURE AMONG UNIVERSITY STUDENTS WHO WORKED ON THESIS - Qodratullah Maha Deva; Amalia Juniarly (Psychology Journal of Mental Health, 2024)
The study aims to determine the role of religious coping on fear of failure among students working on their thesis. The hypothesis in this study is that there is a role of religious coping on fear of failure. The population in this study were students from Islamic-based universities who were working on their thesis. The number of samples in this study consisted of 200 students with 50 students for try out. Sampling in this study used a purposive sampling technique. The fear of failure variable is measured using the proposed by Conroy (2001). To measure religious coping variables, a religious coping scale was used which was compiledfear of failure scale compiled by the researcher referring to the dimensions by researchers referring to the dimensions put forward by Strelhow, Sarriera, and Bedin (2017). Data analysis was used using a simple linear regression technique. The results of the simple regression analysis between religious coping and fear of failure showed that the R square value is 0,031, the F value is 6,230, and the significance value is 0,013 (p>0.05). This shows that religious coping has a significant role in fear of failure. Thus, the hypothesis proposed in this study is accepted.